Interactive Learning Media for Fashion Design Competencies in Training Institutions - Nurul Srikandini; Rina Febriana; Wesnina Wesnina (FKIP - Universitas Riau, 2026)
Vocational fashion training requires effective instructional media to support procedural learning, particularly in pattern-making competencies that involve sequential measurement and construction processes. However, many training institutions still rely on conventional media that provide limited visual guidance and hinder learners’ understanding. This study aims to identify instructional challenges and analyze the needs for interactive learning media in women’s basic pattern-making competencies. A qualitative descriptive approach was employed using a needs analysis design adapted from the preliminary stage of the Borg and Gall development model. Data were collected through structured interviews with five fashion instructors at Pusat Pelatihan Kerja Daerah (PPKD) in Jakarta and analyzed using thematic analysis supported by descriptive statistics. The findings indicate that existing media such as PowerPoint presentations, printed modules, and general online videos are insufficient to support procedural understanding and independent learning. Trainees frequently experience errors in body measurement, pattern proportion, and line construction due to limited visual explanations and time constraints. The study concludes that the development of interactive learning media incorporating step-by-step visualization, simulation features, and immediate feedback is essential to enhance learning effectiveness in vocational fashion training.